2015
DOI: 10.1080/1045988x.2015.1038775
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Superheroes Social Skills to Reduce Disruptive and Aggressive Behavior

Abstract: The current pilot study investigated the effectiveness of the Superheroes Social Skills program in decreasing disruptive and aggressive behavior of elementary-age students with high-incidence disabilities. Six students in a self-contained classroom, identified as displaying high rates of disruptive and aggressive behavior toward peers, were included in the study. Social skills training was presented over 10 lessons that targeted instructional control and turn taking skills. Results indicate immediate improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…& 1.2) which is symbolically important as it can create a sense of motivation and inspiration in the young readers who get fascinated by the fictional characters of super human powers. O"Handley, Radley and Cavell (2016) in their study have also investigated a similar case in which they have concluded that when children are exposed to content which contains superheroes in an educational environment, it can have positive impact on them. (as cited in K. Zeytuncu, 2019) The markers of modality in both covers are enhancing the naturalistic quality of the background.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…& 1.2) which is symbolically important as it can create a sense of motivation and inspiration in the young readers who get fascinated by the fictional characters of super human powers. O"Handley, Radley and Cavell (2016) in their study have also investigated a similar case in which they have concluded that when children are exposed to content which contains superheroes in an educational environment, it can have positive impact on them. (as cited in K. Zeytuncu, 2019) The markers of modality in both covers are enhancing the naturalistic quality of the background.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…High sensation seeking followed by low emotional reactivity, low social skills, and gender (maleness) predicted nonaggressive ASBs. Improvement in social skills has shown to reduce ASBs (O'Handley, Radley, & Cavell, 2015).…”
Section: Sensation Seeking and Subtypes Of Empathy As Predictors Of Smentioning
confidence: 99%
“…This study aims to add to the literature by addressing the question regarding the necessity of implementing the entirety of Superheroes packaged intervention to produce mastery skill levels. This is important when considering school personnel’s time, as a full lesson of Superheroes takes approximately 30 min to an hour to implement (Murphy et al, 2018; O’Handley et al, 2016) whereas implementing only the video component would be substantially shorter in duration. The following research question guided the present investigation:…”
mentioning
confidence: 99%